2021
DOI: 10.3390/jpm12010014
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction among Microbiota, Epigenetic Regulation, and Air Pollutants in Disease Prevention

Abstract: Environmental pollutants can influence microbiota variety, with important implications for the general wellbeing of organisms. In subjects at high-risk of cancer, gut, and lung microbiota are distinct from those of low-risk subjects, and disease progression is associated with microbiota alterations. As with many inflammatory diseases, it is the combination of specific host and environmental factors in certain individuals that provokes disease outcomes. The microbiota metabolites influence activity of epigeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 103 publications
0
10
0
Order By: Relevance
“…The misuse of antibiotics is one of the main causes of the diffusion of antimicrobial-resistant pathogens and genes, that lead to the development of infectious diseases that are harder to threat [63]. Selective pressures favoring ARGs presence and spread are present mainly in hospitals, pharmaceutical implants, and wastewater treatment plants (WWTPs) [64,65]. He et al (2020) reported the presence of the same ARGs that are present in a hospital at a distance of 5 km from the hospital [66].…”
Section: Discussionmentioning
confidence: 99%
“…The misuse of antibiotics is one of the main causes of the diffusion of antimicrobial-resistant pathogens and genes, that lead to the development of infectious diseases that are harder to threat [63]. Selective pressures favoring ARGs presence and spread are present mainly in hospitals, pharmaceutical implants, and wastewater treatment plants (WWTPs) [64,65]. He et al (2020) reported the presence of the same ARGs that are present in a hospital at a distance of 5 km from the hospital [66].…”
Section: Discussionmentioning
confidence: 99%
“…A direct relationship has been reported between exposure to fine particulate matter suspended in the air with intestinal dysbiosis and with obesity [96][97][98], which affects host adiposity through a comprehensive signaling pathways [99]. Environmental pollutants can influence the variety of microbiota, and their metabolites influence the activity of epigenetic enzymes.…”
Section: Organic Interplay Between Pollution and Obesity 41 Digestive...mentioning
confidence: 99%
“…Environmental pollutants can influence the variety of microbiota, and their metabolites influence the activity of epigenetic enzymes. The mechanisms of action of environmental pollution also include the interaction between different niches of the human microbiota, such as the lung-gut axis [96,100] (Figure 3).…”
Section: Organic Interplay Between Pollution and Obesity 41 Digestive...mentioning
confidence: 99%
“…It comprises manuscripts reporting novel data as well as state-of-the-art reviews. The issue begins with five articles [ 1 , 2 , 3 , 4 ] focus on the role of microRNAs in environmental risk factors and lung cancer development.…”
mentioning
confidence: 99%
“…The epigenetic regulations can reprogram differentiated cells in response to environmental changes. In subjects at high risk of cancer, gut and lung microbiota are distinct from those of low-risk subjects, and disease progression is associated with microbiota alterations [ 4 ]. Next in this Special Issue are two contributions describing the relationship between miRNA profiles and oncogene mutations in non-smoker lung cancer and the identification, by microRNA analysis, of environmental risk factors using integrated DNA adducts and microRNAs analyses to retrospectively study the contribution of exposures to environmental carcinogens to lung cancer in 64 non-smokers living in Sicily and Catania city near to the Etna volcano [ 7 ].…”
mentioning
confidence: 99%